PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN INDUSTRI SUBSEKTOR LOGAM DAN SEJENISNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2023 - Adhani, Cindy; Jamaluddin (Journal of Research and Publication Innovation, 2024)
This study aims to determine how the influence of Good Corporate Governance on the financial performance of companies in the Metal subsector industry and the like listed on the Indonesia Stock Exchange (IDX) for the period 2014-2023, based on Good Corporate Governance indicators which are proportioned in the independent board of commissioners, audit committee and managerial ownership method as variables. the research used is quantitative descriptive method and secondary data collection. The population in this study is the financial statements of metal sub-sector industrial companies and the like. Sampling in this study using purposive sampling technique to get samples that match the research criteria. The sample used was 50 samples of 5 company categories in a 10-year period. The results of the research with the t test, show that the independent board of commissioners has no significant effect, institutional ownership has no significant effect, and managerial ownership has no significant effect on financial performance. The results of the f test research variables (Independent Board of Commissioners, Institutional Ownership, and Managerial Ownership) together have no significant effect on financial performance.